Tes Slominski, Trad Nation: Gender, Sexuality, and Race in Irish Traditional Music (2020) (Journal of the Society for Musicology in Ireland, 2021)
A review of Tes Slominski, Trad Nation: Gender, Sexuality, and Race in Irish Traditional Music (Middletown: Wesleyan University Press, 2020). ISBN 9780819579287, 244pp, £19.95 (Hardback).